Conditions for consensus in directed networks of agents with heterogeneous output saturation - Wang, Qingling; Sun, Changyin (IET control theory & applications, 2016)
This study addresses the consensus problem for single-integrator agents with heterogeneous output saturation. By investigating the unique achievable equilibrium and employing an integral Lyapunov function, some conditions of single-integrator agents with heterogeneous and magnitude output saturation are presented. The main contribution of this work is that under the directed graph with strongly connected or a spanning tree, a necessary and sufficient condition for consensus with heterogeneous and magnitude output saturation is first obtained. In addition, some properties of the unachievable consensus are discussed. Finally, simulation examples are given to show the validity of the theoretical results.